Pengaruh Pemberian Probiotik Terhadap Performa Ayam Petelur - Hartono, Madi; Kurtini, Tintin (Jurnal Penelitian Pertanian Terapan, 2015)
This study was conducted to determine the effect of supplements probiotic on layer performance (consumption and conversion ration, persentage hen day and egg weight). This research was held on 21 July?24 August 2014 in the CV. Varia Agung Jaya henhouse laying in the District of Seputih Mataram, Center of Lampung Regency. Local probiotic was made in Microbiology Laboratorium and Moleculer Biology Laboratorium, Faculty of MIPA, Lampung University. The study used completely randomized design with 3 treatments (P1: control ration, P2: control ration with local probiotic 3%, and P3: control ration with comercial probiotic 3%) and 6 replications. Data obtained was analyzed using analysis of variance at 5% level and continued Duncan test at 5% level. Based on the results we can conclude: the effect of treatments significant (P<0.05) on consumption and conversion ration, but no significant (P>0.05) on percentage of hen day and egg weight. Control ration significantly (P<0.05) with control ration with local probiotic 3% and control ration with comercial probiotic 3% on consumption and conversion ration, but no significant (P>0.05) on supplement probiotic. Keywords: probiotics, performance, layer